2019
DOI: 10.1021/acs.est.8b07132
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Induced C-Al2O3-Framework (NiCAF) Supported Core–Multishell Catalysts for Efficient Catalytic Ozonation: A Structure-to-Performance Study

Abstract: During catalytic ozonation, Al2O3-supported catalysts usually have stable structures but relatively low surface activity, while carbon-supported catalysts are opposite. To encourage their synergisms, we designed a Ni-induced C-Al2O3-framework (NiCAF) and reinforced it with a Cu–Co bimetal to create an efficient catalyst (CuCo/NiCAF) with a core–multishell structure. The partial graphitization of carbon adjacent to Ni crystals formed a strong out-shell on the catalyst surface. The rate constant for total organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…Heterogeneous catalytic ozonation (HCO) has been widely studied as a promising approach for the removal of organic contaminants from wastewater. Various earlier studies have reported that the O 3 concentrated on the catalyst surface reacts with active surface sites triggering the production of reactive oxygen species (ROS) such as hydroxyl radicals ( · OH) and/or other radicals which contribute to the oxidation of targeted organic contaminants. For example, Bing et al suggested that by introducing different metal oxides into the structure of mesoporous SBA-15 silica, the decomposition of adsorbed O 3 on the catalyst surface can be manipulated with their results showing that Al 2 O 3 promoted surface atomic oxygen generation while Fe 2 O 3 favored surface · OH and superoxide (O 2 · – ) production. The formation of · OH was also reported to occur via the interaction of adsorbed O 3 with Fe sites in amorphous iron silicate and iron silicate loaded pumice , as well as at aluminum oxide and iron oxy-hydroxide surface sites in light-weight granular mixed-quartz sands .…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous catalytic ozonation (HCO) has been widely studied as a promising approach for the removal of organic contaminants from wastewater. Various earlier studies have reported that the O 3 concentrated on the catalyst surface reacts with active surface sites triggering the production of reactive oxygen species (ROS) such as hydroxyl radicals ( · OH) and/or other radicals which contribute to the oxidation of targeted organic contaminants. For example, Bing et al suggested that by introducing different metal oxides into the structure of mesoporous SBA-15 silica, the decomposition of adsorbed O 3 on the catalyst surface can be manipulated with their results showing that Al 2 O 3 promoted surface atomic oxygen generation while Fe 2 O 3 favored surface · OH and superoxide (O 2 · – ) production. The formation of · OH was also reported to occur via the interaction of adsorbed O 3 with Fe sites in amorphous iron silicate and iron silicate loaded pumice , as well as at aluminum oxide and iron oxy-hydroxide surface sites in light-weight granular mixed-quartz sands .…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used advanced oxidation processes include ozone catalytic oxidation, Fenton/Fenton-like reaction, ultraviolet photocatalysis, and electrochemical oxidation (Hervy et al, 2018;Kou et al, 2018). The rapid development of ozone catalytic oxidation has become a powerful tool for the efficient treatment of refractory organics in advanced oxidation processes (Wei et al, 2019).…”
Section: Research Articlementioning
confidence: 99%
“…can improve the catalytic performance dramatically, ,,, while the carbon structure may lose the structural integrity in the process of frictions and collisions between catalysts. In order to promote the mechanical strength, the Ni-induced C–Al 2 O 3 framework (CAF) was proposed . Its graphitized carbon out-shell decorated with bimetal elements of Cu–Co increased the active sites, reaction routines, and surface mass-transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the rigid Al 2 O 3 core maintained its mechanical stability. However, Ni has high catalytic graphitization ability while it exhibits limited catalytic performance in the CAF structure . There are other metals that possess both catalytic graphitization ability and high catalytic ozonation performance such as Fe, which has not been studied for CAF yet.…”
Section: Introductionmentioning
confidence: 99%